2021
DOI: 10.1186/s12984-021-00856-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting telerobotics for sensorimotor rehabilitation: a locomotor embodiment

Abstract: Background Manual treadmill training is used for rehabilitating locomotor impairments but can be physically demanding for trainers. This has been addressed by enlisting robots, but in doing so, the ability of trainers to use their experience and judgment to modulate locomotor assistance on the fly has been lost. This paper explores the feasibility of a telerobotics approach for locomotor training that allows patients to receive remote physical assistance from trainers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Initially, they were used to augment pharmacy and laboratory services. With the introduction of the DaVinci system, a new era in healthcare was delivered, demonstrating that surgery may be less burdensome and taxing, thus resulting in more favorable outcomes [133][134][135][136]. Surgical robotic systems are revolutionary in surgery, nonetheless, and their introduction in anesthesia is relatively slow [137].…”
Section: Innovation In Servicementioning
confidence: 99%
“…Initially, they were used to augment pharmacy and laboratory services. With the introduction of the DaVinci system, a new era in healthcare was delivered, demonstrating that surgery may be less burdensome and taxing, thus resulting in more favorable outcomes [133][134][135][136]. Surgical robotic systems are revolutionary in surgery, nonetheless, and their introduction in anesthesia is relatively slow [137].…”
Section: Innovation In Servicementioning
confidence: 99%
“…These programs show the exercises to be followed by the patient and which the patient must then record for follow-up (11,12,13,14). In the context of teleoperated physical rehabilitation, the studies found are mostly performed on the upper extremity (15,16,17,18) and a few on the lower extremity (19,20). However, these solutions did not integrate the Industry 4.0 model into their proposal.…”
Section: Introductionmentioning
confidence: 99%